Depression status decreased Quality Of Life among postpartum mother - Lastri Mei Winarni (International Journal of Health Science and Technology, 2021)
Purpose : to know correlation between depression symptoms and the quality of life (QoL) among postpartum mother. Method of the study was used quasi experimental design by  pre and post test with control group. The  respondents are 54 mothers. The study was conducted at maternal clinic. Statistical analysis used Pearson and simple linear regression. Result of the study there is correlation between depression symptoms and the QoL among postpartum mothers with r count values r table values (0.030 0.05). The correlation direction was negative, the higher depression symptoms, the -0.296 times the QoL of mothers decreased.